Superparamagnetic Iron Oxide–Enhanced Magnetic Resonance Imaging of Neuroinflammation in a Rat Model of Radicular Pain - Daniel L.J. Thorek; Christine L. Weisshaar; Julie C. Czupryna; Beth A. Winkelstein; Andrew Tsourkas (Molecular Imaging)
In many clinical cases of radicular pain, no noticeable neuropathology is detected by conventional medical imaging strategies. Superparamagnetic iron oxide (SPIO) nanoparticles were evaluated as magnetic resonance contrast agents to specifically detect neuroinflammation at sites of painful injury in a rat model of cervical nerve root compression. Two separate groups of rats were used: an injury group that underwent controlled transient compression of the dorsal root and a sham group that received the same surgical procedures but no injury. Precontrast magnetic resonance imaging (MRI) was performed 6 days after surgery, followed by administration of SPIO via tail vein injection. After 24 hours, T 2 * -weighted imaging at the site of root injury revealed a postcontrast enhancement of 72.9 ± 31%. This was significantly greater than that of injured animals prior to SPIO administration (5.3 ± 12.9%). SPIO did not generate any significant postcontrast enhancement in the nerve roots of the sham group. Histology confirmed colocalization of SPIO with macrophage at the injury site. These findings suggest that SPIO-enhanced MRI may be a valuable tool to identify otherwise undetectable nerve root compression and enable improved patient management.